Hiperrealitas Unggahan Outfit of the Day di Instagram: Studi Kasus Unggahan Instagram Pengunjung Seduh Café, Kabupaten Tuban: Hyperreality of Outfit of the Day Posts on Instagram: A Case Study of Instagram Posts of Seduh Café Visitors, Tuban Regency - Sutriwana; Hidayat, Medhy Aginta; Suktomansyah, Andi Muh. (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2024)
This article aims to understand the phenomenon of hyperreality in the OOTD (Outfit of The Day) fashion uploads of visitors to Seduh Cafe in Pantai Kelapa, Tuban Regency, through the social media platform Instagram. This phenomenon is interesting because OOTD on Instagram often creates a world of hyperreality, where the boundaries between the real and the artificial become blurred. This research uses hyperreality theory, which suggests that the distinction between the real and the artificial has disappeared. The method used in this research is qualitative with a case study approach. Data were collected through observation, in-depth interviews, and documentation techniques. The data analysis technique follows the Miles and Huberman model which consists of three stages: data reduction, data presentation, and conclusion drawing. The results showed that to display the ideal OOTD fashion, visitors to Seduh Cafe in Kelapa Beach often simulate their OOTD in various ways that exceed their original identity. This indicates that OOTD visitors to Seduh Cafe can create a world of hyperreality on Instagram, because every action they take has been simulated. Without realizing it, these visitors manipulate reality to cover the original reality, so that there is no longer a clear distinction between the real and the artificial. In fact, the artificial reality becomes more convincing and has drowned out the original reality itself.